2012
DOI: 10.1057/jphp.2012.31
|View full text |Cite
|
Sign up to set email alerts
|

Operational research and HIV policy and guidelines: Lessons from a study of patients lost to follow-up from a public antiretroviral treatment program in Cameroon

Abstract: Can operations and implementation research guide today's unprecedented efforts to scale-up HIV/AIDS prevention, treatment, care, and support in resource-limited settings? Our study of patients with HIV/AIDS who were first seen at the Central Hospital (Yaoundé, Cameroon) to begin antiretroviral therapy demonstrates the value of using operations research to explore programs, policies, and guidelines used in health care. We studied one group of patients, those lost to follow-up. Our findings confirmed the value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…We excluded 1589 items for the reasons detailed in Figure . Thirty articles met inclusion criteria . Two studies reported results for children and adults separately.…”
Section: Resultsmentioning
confidence: 99%
“…We excluded 1589 items for the reasons detailed in Figure . Thirty articles met inclusion criteria . Two studies reported results for children and adults separately.…”
Section: Resultsmentioning
confidence: 99%
“…As the number of sites providing ART increases, patient mobility is likely to become more common and should be supported by increasing patient awareness and understanding of transfer procedures (Mben et al . ), removing any pre‐conditions for transfer (Wubshet et al . ), simplifying facility processes for transfer (Miller et al .…”
Section: Discussionmentioning
confidence: 99%
“…Self‐transfers may occur for both health system and personal reasons including facility congestion and perceptions of depersonalised services, permanent or temporary relocation, lack of patient awareness of transferring processes and ease of transferring without documentation due to increasing numbers of ART providers (Mben et al . ; Nglazi et al . ; Wubshet et al .…”
Section: Introductionmentioning
confidence: 99%
“… 37 Operational research has helped to influence practice and policy for several infectious diseases. Examples include the SAFE (Surgery [for trichiasis]–Antibiotics–Facial cleanliness–Environmental improvement) strategy for trachoma, 38 expanding coverage of HAART, 39 41 evaluating pre-HAART, 42 evaluating surveillance for malaria elimination, 43 improving the management of HIV–TB coinfection, 44 evaluating cotrimoxazole preventive therapy, 45 improving the diagnosis and management of recurrent TB, 46 preventing mother-to-child transmission of HIV, 47 and the preventive treatment of malaria in infants. 48 In their paper on the concepts, contributions, and challenges on operational research, Zachariah et al provide 16 examples of how it has improved medical care and practice, been used to assess the feasibility of interventions, and been used to advocate policy change.…”
Section: Impact Of Infectious Disease Research On Healthmentioning
confidence: 99%